2013
DOI: 10.1186/2193-1801-2-632
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus spp. isolation from excreta of pigeons (Columba livia) in and around Monterrey, Mexico

Abstract: The presence of Cryptococcus spp. has been reported in Mexico’s capital city; however, to our knowledge there are no reports of its presence in the state of Nuevo León located in northeast Mexico. This is presumed to be because the hot and dry climate in this region does not favor cryptococcal proliferation. This study confirmed the presence of C. neoformans and C. albidus in 20% (10/50) of randomly selected fecal samples of pigeons (Columba livia) in the Monterrey metropolitan area. The presence of this yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Other species of Cryptococcus are considered potentially pathogenic, such as C. laurentii (currently Papiliotrema laurentii), C. albidus (currently Naganishia albida), and C. flavescens (currently P. flavescens), which have been reported in some studies [6,7,17,18,19]. These species are also isolated from the environment in organic matter, such as tree debris and bird excreta [7,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Other species of Cryptococcus are considered potentially pathogenic, such as C. laurentii (currently Papiliotrema laurentii), C. albidus (currently Naganishia albida), and C. flavescens (currently P. flavescens), which have been reported in some studies [6,7,17,18,19]. These species are also isolated from the environment in organic matter, such as tree debris and bird excreta [7,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Data from Bolivia, Costa Rica, Dominican Republic, El Salvador, Haiti, Nicaragua, and Panama about the molecular typing of cryptococcal strains has not been reported. a : C. neoformans has been mostly recovered from avian droppings, decaying organic matter, and soil ( Casali et al 2003 , Ribeiro et al 2006 , Lugarini et al 2008 , Ribeiro and Ngamskulrungroj 2008 , Andrade-Silva et al 2010 , Illnait-Zaragozi et al 2010a , Souza et al 2010 , Ferreira-Paim et al 2011 , Canónico-González et al 2013 , Castro e Silva et al 2016 ). C. gattii is associated with several tree species ( Escandón et al 2006 , Trilles et al 2008 , Costa et al 2009 , Refojo et al 2009 , Escandón et al 2010 , Firacative et al 2011 , Mazza et al 2013 , Anzai et al 2014 , Cattana et al 2014 , Brito-Santos et al 2015 , Vélez and Escandón 2017 ).…”
mentioning
confidence: 99%
“…In our region, one study has reported the isolation of C. neoformans var. grubii and C. albidus, but only pigeon's excreta were sampled (Canónico-González et al 2013). In Mexico City, there was one report of C. gattii isolation in a sample from Eucalyptus camaldulensis (Arguero Licea and Cervantes Olivares 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This region has a dry, hot climate with summer temperatures ranging from 35 to 40°C, which could be considered as not suitable for environmental spread of Cryptococcus spp. (Canónico-González et al 2013). Thus, the aims of this study were to determine the prevalence of the molecular types of C. neoformans/C.…”
Section: Introductionmentioning
confidence: 93%